Estimation of CH4 emissions from the East Siberian Arctic Shelf based on atmospheric observations aboard the R/V Mirai during fall cruises from 2012 to 2017 - Tohjima, Yasunori; Zeng, Jiye; Shirai, Tomoko; Niwa, Yosuke; Ishidoya, Shigeyuki; Taketani, Fumikazu; Sasano, Daisuke; Kosugi, Naohiro; Kameyama, Sohiko; Takashima, Hisahiro; Nara, Hideki; Morimoto, Shinji (Polar Science, 2021)
Atmospheric CH4 mole fractions were observed aboard the R/V Mirai sailing in waters off Alaska in the Arctic Ocean in September 2012–2017 to investigate the CH4 emissions from the surrounding region, especially from the East Siberian Arctic Shelf (ESAS). The synoptic-scale increases of CH4 were compared with simulated increases based on a Lagrangian Particle Dispersion Model and monthly CH4 flux maps determined by a global atmospheric inversion system. There were good agreements between the observed and simulated CH4 increases, suggesting the validity of CH4 fluxes from the surrounding areas of the cruise experiments. The CH4 emissions from the ESAS in September were further optimized in order to minimize the root mean square of the differences between the observed and simulated CH4 increases. The average (±1σ) of the resulting emission rates was 0.58 ± 0.47 TgCH4 yr−1, which was much smaller than previously reported estimates. The individual optimized CH4 emissions varied from −0.1 ± 0.3 to 1.3 ± 0.4 TgCH4 yr−1, showing a positive correlation with the sea surface temperature and a negative correlation with the ice concentration of the ESAS area in September. These results suggest a possible enhancement of the CH4 emissions from the ESAS in a warmer future. journal article